Hybrid 3D/2D NH2-UIO-66/h-BN nanostructures for smart epoxy coatings with enhanced anti-corrosion and mechanical performance - Ali Dashan; Fatemeh Norouzi; Mohammad Ramezanzadeh; Bahram Ramezanzadeh (Journal of Materials Research and Technology, 2025)
This study introduces an innovative epoxy coating system enhanced with 2D hexagonal boron nitride (h-BN) nanosheets, commonly called white graphene. These nanosheets have been surface-modified with APTES and UIO-66-NH2 (NH2-UIO) particles to improve nanoparticle dispersion within the epoxy matrix. The NH2-UIO particles also allow for incorporating green mono-sodium glutamate-zinc inhibitors within their porosity, providing both active corrosion protection and enhanced mechanical properties. The structure, composition, and surface chemistry of the nanomaterials were characterized using XRD, FT-IR, TGA, XPS, BET, TEM, and FE-SEM/EDAX-Mapping techniques. The anti-corrosion performance was assessed through EIS, pull-off adhesion, cathodic disbondment, and ICP analysis. Thermo-mechanical behavior was evaluated using DMTA, tensile testing, and FE-SEM of the fracture surfaces. EIS tests revealed that the nanoparticle-filled coatings exhibited active corrosion protection. The scratched coating exhibited an impedance of 128.22 kΩ cm2 after 3 h immersion, an improvement of 104.8 % compared to the control's 62.59 kΩ cm2, highlighting its efficient active protection. Over a longer period, the nanoparticle-filled coatings maintained a resistance of 4.73 GΩ cm2 after 70 days of exposure to saline media, significantly outperforming the control sample, which displayed a resistance of just 0.011 GΩ cm2. Adhesion tests, including pull-off and cathodic disbondment, showed enhanced adhesion in the modified coatings, with a 77 % reduction in adhesion loss and 42 % less disbondment compared to uninhibited samples. Additionally, the incorporation of nanoparticles resulted in substantial improvements in mechanical performance, such as increased hardness, Young's modulus, tensile strength, and higher cross-link density.